Arid Lands Information Network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Arid Lands Information Network (ALIN) is principally for field workers, project managers, group leaders and local government officials. ALIN is a British NGO, based in Dakar, Senegal, which is designed to help people working in the field to...